2016
DOI: 10.1210/jc.2016-2080
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Estrogen Regulates Somatostatin-Induced Rebound GH Secretion in Postmenopausal Women

Abstract: Background: Systemic concentrations of T, estradiol (E2), GH, IGF-1, and IGF binding protein-3 decline in healthy aging individuals. Conversely, T and E2 stimulate GH and IGF-1 production in hypogonadal patients. Hypothesis: Because E2 stimulates GH secretion, putatively via the nuclear estrogen receptor-α and E2 and GH fall with menopause, we postulated that diminished endogenous E2 contributes to low GH output in older wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The effects of E2 on GH secretion after menopause were confirmed in a double-blind, controlled study in which plasma GH was analyzed before and after somatostatin infusion in healthy post-menopausal women treated with placebo or with an inhibitor of aromatase or a selective inhibitor of the E2 receptor. In this study a 1-h GH peak rebound after somatostatin infusion was clearly decreased during both estrogen-deprivation protocols (80). This study concluded that GH secretion after menopause depends on low levels of ovarian estrogens, and also confirms our previous postulate about that the interruption of somatostatin release induces the synthesis and secretion of GH via GHRH (9), and that sex steroids act on GH neuroregulation by inhibiting somatostatin secretion via alpha-2 noradrenergic pathways (9).…”
Section: Ovarian Functioningmentioning
confidence: 58%
“…The effects of E2 on GH secretion after menopause were confirmed in a double-blind, controlled study in which plasma GH was analyzed before and after somatostatin infusion in healthy post-menopausal women treated with placebo or with an inhibitor of aromatase or a selective inhibitor of the E2 receptor. In this study a 1-h GH peak rebound after somatostatin infusion was clearly decreased during both estrogen-deprivation protocols (80). This study concluded that GH secretion after menopause depends on low levels of ovarian estrogens, and also confirms our previous postulate about that the interruption of somatostatin release induces the synthesis and secretion of GH via GHRH (9), and that sex steroids act on GH neuroregulation by inhibiting somatostatin secretion via alpha-2 noradrenergic pathways (9).…”
Section: Ovarian Functioningmentioning
confidence: 58%
“…SARS‐CoV‐2 aggressiveness has been shown to be gender dependent and higher in males (1). Intriguingly, it is well known that GH secretion is, overall, greater in women of all ages than in men, and that sex steroids can on the one hand influence GH secretion and on the other hand alter IGF1 local synthesis in target tissues as well as the expression of the GH receptor (2). It has also been reported that the percentage of SARS‐CoV‐2 registered cases in China increased progressively with age, as it was 1% in 10‐ to 19‐year‐olds, 8% in 20‐ to 29‐year‐olds, and 87% in 30‐ to 79‐year‐olds (1).…”
mentioning
confidence: 99%
“…However, a recent randomized, doubleblind, controlled study, performed in 60 healthy postmenopausal women conclude that while there was a E2 decrease when giving anastrozole (an inhibitor of aromatase activity), but no changes in E2 levels were observed when fulvestrant (a selective estrogen receptor-α antagonist) was administered. In spite of it, GH rebound after SS infusion declined markedly during both estrogen-deprivation schedules, suggesting a previously unrecognized dependence of hypothalamic-pituitary GH regulation on low levels of endogenous estrogen during menopause [147].…”
Section: Control Of Ss By Sex Steroids Depending On the Sex The Testi...mentioning
confidence: 88%